2019
DOI: 10.12968/jowc.2019.28.sup9.s14
|View full text |Cite
|
Sign up to set email alerts
|

Health economics for treatment of diabetic foot ulcers: a cost-effectiveness analysis of eight skin substitutes

Abstract: Aim: Skin substitutes are frequently used to treat chronic diabetic foot ulcers (DFU), and many different options are available. While the clinical efficacy of many products has been evaluated, a comprehensive cost-effectiveness analysis comparing the most popular skin substitutes and using the most recent cost data has been lacking. Methods: This study compared eight skin substitutes using published efficacy rates combined with the Centers for Medicare and Medicaid Services (CMS) 2018 cost data. The study cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…While other alternatives could compensate for these disadvantages, a less time-consuming approach—such as a free flap—would have implied greater risks in our case due to the patient’s previous exposure to radiation which affected adequate vascularization of the affected tissue. Regarding wound healing costs, Samsell et al 9 compared cost-effectiveness among several skin-substitute products in the management of diabetic foot ulcers. Products, such as DermACELL (D, LifeNet Health; Virgina Beach, Va.), EpiFix (EF, MiMedx; Marietta, Ga.), and Integra Dermal Regeneration Template (IDRT, Integra LifeSciences; Plainsboro, N.J.), among others, were studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While other alternatives could compensate for these disadvantages, a less time-consuming approach—such as a free flap—would have implied greater risks in our case due to the patient’s previous exposure to radiation which affected adequate vascularization of the affected tissue. Regarding wound healing costs, Samsell et al 9 compared cost-effectiveness among several skin-substitute products in the management of diabetic foot ulcers. Products, such as DermACELL (D, LifeNet Health; Virgina Beach, Va.), EpiFix (EF, MiMedx; Marietta, Ga.), and Integra Dermal Regeneration Template (IDRT, Integra LifeSciences; Plainsboro, N.J.), among others, were studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Integra DRT had a product cost per application of $901.01, but a cost per treated wound of $1802.02. 9 This article was used as reference and analyzed by PolarityTE Inc.—the SkinTE manufacturer company—to compare SkinTE costs with these skin-substitute alternatives. The interim analysis revealed that SkinTE cost was 61% lower than the mean cost of product per treated wound reported by Samsell et al, 9 with a mean total cost of around $1300; 10 however, costs may vary depending on the wound size and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of a recent health economics study examining the cost-effectiveness of 8 common CTPs in the treatment of DFUs using 2018 Medicare reimbursement costs and efficacy rates from the associated RCTs reported that the percentage of wounds healed per $1000 expenditure with each patient ranged from 3.9-26.5 DFUs in the hospital outpatient department, and 4.3-36.4 DFUs in the physicians' office setting 36 . In addition, the authors noted that costs of each CTP did not necessarily correlate with healing efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…64 Some studies, however, suggest that Apligraf may not be the most cost-effective skin substitute available. [64][65][66][67] TheraSkin (LifeNet Health, Virginia Beach, VA [procurement and processing] and Solsys Medical, Newport News, VA [distribution]) is a cadaveric-derived epidermal and dermal replacement. Tissue is harvested within 24 hours postmortem from an organ donor who cleared standard safety screenings for organ procurement.…”
Section: Cellular Skin Substitutesmentioning
confidence: 99%